Spectroscopic diagnostics of lead stratification in hot subdwarf atmospheres - Scott, L. J.A.; Jeffery, C. S.; Byrne, C. M.; Dorsch, Matti (Monthly Notices of the Royal Astronomical Society, 2024)
Heavy metal subdwarfs are a class of hot subdwarfs with very high abundances of heavy elements, typically around 10 000 times solar. They include stars, which are strongly enhanced in either lead or zirconium, as well as other elements. Vertical stratification of the enhanced elements, where the element is concentrated in a thin layer of the atmosphere, has been proposed as a mechanism to explain the apparent high abundances. This paper explores the effects of the vertical stratification of lead on the theoretical spectra of hot subdwarfs. The concentration of lead in different regions of the model atmosphere is found to affect individual lines in a broadly wavelength-dependent manner, with the potential for lines to display modified profiles depending on the location of lead enhancement in the atmosphere. This wavelength dependence highlights the importance of observations in both the optical and the UV for determining whether stratification is present in real stars.
CRIS-Team Scopus Importer:2024-05-10
Keywords: diffusion; line: profiles; radiative transfer; stars: atmospheres; stars: chemically peculiar; subdwarfs